Comparison of Spider-Robot Information Models - Kravchenko, Viktor V.; Efremov, Artem A.; Zhilenkov, Anton A.; Kozlov, Vladimir N.; Silkin, Artem A.; Moiseev, Ilya S.; Krupinin, Oleg; Lebedeva, Ekaterina (Universitas Muhammadiyah Yogyakarta, 2023)
The paper deduces a mathematical model of a spider-robot with six three-link limbs. Many limbs with a multi-link structure greatly complicate the process of synthesizing a model, since in total the robot has twenty-four degrees of freedom, i.e., three coordinates of the center of mass of the body in space, three angles of rotation of the body relative to its center of mass and three degrees of freedom for each limb, to describe the position of the links. The derived mathematical model is based on the Lagrange equations with a further transformation of the equations to the Cauchy normal form in a matrix form. To test the resulting model in a SimInTech environment, an information model is synthesized and two simple experiments ar carried out to simulate the behavior of real spiders: moving forward in a straight line and turning in place at a given angle. The experimental results demonstrate that the synthesized information model can well cope with the tasks and the mathematical model underlying it can be used for further research.